If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8n+4(1+5n)=-6n
We simplify the equation to the form, which is simple to understand
-8n+4(1+5n)=-6n
Reorder the terms in parentheses
-8n+(+4+20n)=-6n
Remove unnecessary parentheses
-8n+4+20n=-6n
We move all terms containing n to the left and all other terms to the right.
-8n+20n+6n=-4
We simplify left and right side of the equation.
+18n=-4
We divide both sides of the equation by 18 to get n.
n=-0.222222222222
| 4t-16+8y=-4 | | -4n-40=79-2n+2 | | -8n+4(2+5n)=-6n-14 | | 7a-3=4+6a | | y=(1/2)/(6/18) | | 9x^2+24x+9=0 | | 90-(5x+10)=90-(x+2) | | 5x^2+x-10=0 | | 63-3x=11-9x | | 0x+11=71-3x | | 5x-94=2x-7 | | 4x-8-2x=x-2 | | 5(4-3)=19 | | 2(5-4)=2 | | 6x+2x^2+1=1 | | 2(30-12)=18 | | 4a^2+625b^4=0 | | 4n+55=8 | | x^4-4x^2+1=0 | | 26=6 | | 14-10x=36-24x | | 8x^4+28x^3-30x^2+11x-2=0 | | 3(6x-14)=12x+6(x-3) | | 1x+10=91+x | | 3(15+2x)-60+9x=0 | | 1.875x+2.125y=97.1 | | 2x+1/3=17 | | 2x+4d+6x-5c+4f= | | (x^2+x)(x+6)=7x | | 10x+30=8x+20 | | 2y-30=0 | | y=400+.25(0) |